Culinary Caravan:Unveiling Klang Valley's food truck frenzy and culture - Abdullah, Norhidayah; Ishak, Noriza; Saad, Mazni; Abukhalifeh, Alaa Nimer (e-International Publishing House, Ltd., UK., 2023)
Investigating the relationships between product quality, food premises and food handlers' cleanliness and customer hygiene satisfaction yielded a crucial implication. The 116 customers of food trucks in Klang Valley revealed the cleanliness attributes related to their hygiene satisfaction. The regression analysis shows that food product quality was the most significant predictor. This study's findings can contribute valuably to improving cleanliness practices among food truck food handlers, serving as a foundation for promoting cleanliness standards within the Malaysia Food Truck Association.